2011
DOI: 10.1038/nature09677
|View full text |Cite
|
Sign up to set email alerts
|

SMAD4-dependent barrier constrains prostate cancer growth and metastatic progression

Abstract: Effective clinical management of prostate cancer (PCA) has been challenged by significant intratumoural heterogeneity on the genomic and pathological levels and limited understanding of the genetic elements governing disease progression1. Here,we exploited the experimental merits of the mouse to test the hypothesis that pathways constraining progression might be activated in indolent Pten-null mouse prostate tumours and that inactivation of such progression barriers in mice would engender a metastasis-prone co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

39
507
3
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 466 publications
(555 citation statements)
references
References 32 publications
39
507
3
1
Order By: Relevance
“…Although multiple prior studies have related genomic markers to PCa clinical outcomes [17][18][19][20]51], the development of GPS specifically addresses the impact of tumor sampling in predicting aggressive PCa and included central pathology review and a large number of clinical recurrence events providing robust statistical power. By adding independent molecular information to established risk parameters, the GPS improves risk stratification at time of diagnosis and may favorably shift the balance of risks and benefits for men who are candidates for AS and facing challenging decisions regarding optimal management of localized PCa.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although multiple prior studies have related genomic markers to PCa clinical outcomes [17][18][19][20]51], the development of GPS specifically addresses the impact of tumor sampling in predicting aggressive PCa and included central pathology review and a large number of clinical recurrence events providing robust statistical power. By adding independent molecular information to established risk parameters, the GPS improves risk stratification at time of diagnosis and may favorably shift the balance of risks and benefits for men who are candidates for AS and facing challenging decisions regarding optimal management of localized PCa.…”
Section: Discussionmentioning
confidence: 99%
“…Although many groups have demonstrated the potential of gene expression analysis to predict outcome in localized PCa [17][18][19][20], frequent genetic differences between regions of individual tumors and limited tumor sampling by needle biopsy pose challenges to molecular-based assays in PCa [21,22]. With these challenges in mind, we conducted two studies to identify genes for which expression in both prostatectomy and biopsy tissues consistently correlates with tumor aggressiveness regardless of multifocality, heterogeneity, or technical challenges associated with limited tumor obtained through biopsy.…”
Section: Introductionmentioning
confidence: 99%
“…Quantitative immunohistochemistry or immunofluorescence assays are being developed that can accurately validate on tissue microarrays (TMAs) the expression of DNA/RNA signatures identified by whole‐tumor profiling; these techniques have the advantage of being highly reproducible and easily applicable for standardized tumor typing/grading, inter‐patient comparisons, and the dissection of intra‐tumoral heterogeneity. Recent applications of such TMA‐based technologies have validated prognostic gene signatures for several tumor types, including prostate and lung cancer (Anagnostou et al., 2011; Dimou et al., 2011; Ding et al., 2011; Zender and Lowe, 2008). Furthermore, the development of sophisticated computer‐based methodologies for TMA analysis (Beck et al., 2011) may facilitate better standardization of the results and also quantitatively assess clinically significant morphometric parameters (e.g., epithelial–stromal ratio, multiple nuclear pleomorphisms, etc…) that would escape conventional pathological examination.…”
Section: Discussionmentioning
confidence: 99%
“…Increasingly sophisticated bioinformatics tools have been applied to such databases, revealing gene signatures of coordinately up‐ and down‐regulated gene transcripts that correlate with and can thereby identify particular tumor subtypes and stages of progression, and in some cases predict prognosis (Golub et al, 1999; Quackenbush, 2006; Reis‐Filho and Pusztai, 2011; Sotiriou and Piccart, 2007, 2009; van't Veer and Bernards, 2008; Walther et al., 2009). Moreover, cross‐filtering of cognate mouse and human tumor transcriptome databases is proving useful in reducing complexity and potentially identifying functionally significant alterations from amongst the “white noise” of non‐specific consequential variation (Ding et al., 2011; Zender and Lowe, 2008). …”
Section: Addressing Tumor Heterogeneity and Complexitymentioning
confidence: 99%
“…However, tumors bearing PTEN mutations in mice are indolent, which barely develop into the invasive carcinoma and display a minimal metastatic incidence. 2 Recently, Ding et al 3 demonstrated that breakdown of the PTEN mutation-induced transforming growth factor (TGF)-b barrier is a rate limit step for prostate cancer metastasis, underscoring the notion that the feedback pathways suppressing progression might be activated in indolent PTEN-null tumors, and inhibition of such progression barriers would develop aggressive metastasis-prone cancer. Therefore, it is important to identify the pathways or players serving as the 'second hit' to abrogate the TGF-b-dependent growth barrier and enable PTEN-null tumors to acquire fully penetrated metastatic potential, which will have important therapeutic implications for the development of new targets or biomarkers for cancer intervention and clinical diagnosis.…”
mentioning
confidence: 99%